2016
DOI: 10.1016/j.jphotobiol.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of plant-pathogenic fungus Colletotrichum acutatum with natural plant-produced photosensitizers under solar radiation

Abstract: 23The increasing tolerance to currently used fungicides and the need for environmentally

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 55 publications
0
34
0
Order By: Relevance
“…We supposed that in the field such concentration will have no effect on plants treated by spraying. Nevertheless, studies on plant pathogens as fungi showed that a concentration up to 50 μ M of natural and synthetic photosensitizers was required to eradicate fungi (De Menezes et al , , Fracarolli et al ). At this threshold concentration of cationic porphyrins, Arabidopsis and pathogens will be most likely eradicated whereas this concentration does not kill tomato plantlets (Guillaumot et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We supposed that in the field such concentration will have no effect on plants treated by spraying. Nevertheless, studies on plant pathogens as fungi showed that a concentration up to 50 μ M of natural and synthetic photosensitizers was required to eradicate fungi (De Menezes et al , , Fracarolli et al ). At this threshold concentration of cationic porphyrins, Arabidopsis and pathogens will be most likely eradicated whereas this concentration does not kill tomato plantlets (Guillaumot et al ).…”
Section: Discussionmentioning
confidence: 99%
“…It could be envisaged as a farming practice in order to eradicate plant pathogens as bacteria and fungi that cause serious threats by drastically reducing crops yield. Studies focusing on the side effects of APDT directly on plants are rare (De Menezes et al , , Fracarolli et al , De Menezes et al , Guillaumot et al , Gonzales et al 2017). However, such studies are required to evaluate the efficiency of APDT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porphyrins and chlorins such as chlorophyllin, have been shown to be very effective against bacteria on kiwi leaves tested in vitro (Jesus et al 2018;Glueck et al 2019). Coumarins, furocoumarin and phenothiazinium were shown to be active against the plant-infecting fungi Colletrichum acuratum and Aspergillus nidulans (De Menezes et al a, b;2014;Fracarolli et al 2016). Finally, when tested on Citrus sinensis petals and leaves, methylene blue was able to kill the Colletotrichum abscissum fungus and proved to be harmless to plant organs; in addition, this treatment did not induce any secondary resistance (Gonzales et al 2017) Previous research works explored the in vitro phenotypical and molecular responses of Arabidopsis and tomato plantlets to the photodynamic stress induced by an exogenous supply of PS (Guillaumot et al 2016;Issawi et al 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Furocoumarins (FCs), also named psoralens, are naturally occurring metabolites in the plants belonging to the Rutaceae and Umbelliferae families, in which they are produced as a chemical defence in response to stress, fungi, bacteria, and insects . With their ambiguous effects on human health, FCs have been widely investigated and have attracted great interest in comparison with the other two classes of molecules reported here.…”
Section: Introductionmentioning
confidence: 99%